Podocytes in health and glomerular disease - Cunanan, Joanna; Zhang, Daniel; Peired, Anna Julie; Barua, Moumita (Frontiers in Cell and Developmental Biology, 2025)
Podocytes are highly specialized, terminally differentiated cells in the glomerulus of the kidney and these cells play a central role in blood filtration. In this review, we comprehensively describe the cell biology of podocytes under healthy conditions and in glomerular disorders wherein podocyte injury is a major pathological mechanism. First, the molecular mechanisms that maintain podocyte actin cytoskeleton structure, permanent cell cycle exit, and metabolism under healthy conditions are described. Secondly, the mechanisms of podocyte injury, including genetic alterations and external insults that ultimately disrupt podocyte actin cytoskeleton dynamics or interrupt podocyte quiescence and mitochondrial metabolism are discussed. This understanding forms the basis of described potential therapeutic agents that act by modulating dysregulated podocyte cytoskeleton organization, prevent or reverse cell cycle re-entry, and re-establish normal mitochondrial energy production. Lastly, the application of modern techniques such as single cell RNA sequencing, super resolution microscopy, atomic force microscopy, and glomerular organoids is improving the resolution of mechanistic podocytopathy knowledge. Taken together, our review provides critical insights into the cellular and molecular mechanisms leading to podocyte loss, necessary for the advancement of therapeutic development in glomerular diseases.